Ekspolarasi Pola Kepemimpinan Yang Didambakan Oleh Karyawan Hotel Holiday Inn Baruna Bali - Ratih Pitaloka, Kadek; Rahmawati, Putu Indah (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study aims to identify and describe the type of leadership desired by employees at the Holiday Inn Baruna Bali hotel. This study is a type of qualitative research. The data sources used in the study are primary data and secondary data. In this study, the data obtained through various research methods such as interviews, observations, and documentation. This study applies qualitative descriptive data analysis techniques. The results of the study indicate that employees of the Holiday Inn Bali Hotel crave leaders who not only have good managerial skills but also have empathy, brotherhood, and are able to create a comfortable work environment and support employee professional development. By implementing more open, communicative leadership, and oriented towards team welfare, employee performance can be more optimal and create more harmonious working relationships in the hotel environment.